Can African traditional culture offer something of value to global approaches in teaching philosophy and religion? - Giddy, Patrick (University of the Free State, 2013)
What characterises the dominant global culture is a kind of autism, the loss of a well-articulated sense of self, a reluctance to spell out its core values and aims. A good education system, on the contrary, helps the learner articulate his/her sense of self in more adequate ways and so become a more self-aware and self-directing learner. In the context of African traditional culture, this will mean engaging with the pre-philosophical expressions of self-understanding, which will have to be considered in the context of modernity. The differentiation of consciousness that is at the heart of our ability to do this, however, is only articulated within a philosophical framework that has not lost the foundational notion of the presence to self of the questioning subject. In what follows I develop this contention for general philosophy, for ethics, for the philosophy of religion, and for how philosophy is presented in an African cultural context. This article is an attempt to show the underlying unity of these topics and thus make my point more effective.
Keywords: African traditional culture; Philosophy; Religion; Ethics